丙烷预冷混合制冷剂液化工艺控制方式优选 - Pan Hongyu; Li Shunli; Li Yuxing; Zhu Jianlu (Zhileng xuebao)
Propane pre-cooling and mixed-refrigerant process, an efficient and simple process and a combination of cascading liquefaction and mixed-refrigerant liquefaction processes, is the most common natural gas liquefaction process by now. Due to the interference of external factors in the actual situation, it is necessary to maintain the stability of liquefaction plant by the controller. Hence the dynamic simulation analysis for the liquefaction process control system is needed. In this paper, the flexibility of liquid level control, temperature control and cascade control in the systems of propane pre-cooling and mixed-refrigerant process is simulated respectively by dynamic simulation, and then the response of liquefaction process and the responding time to stability can be known by changing the settings of controller. In this way, the optimal control mode of each system has been got. It indicates that the systems have better stability and faster responding speed when the propane pre-cooling system adopts liquid level control or cascade control, mixed refrigerant process applies the liquid level control, and the gas system uses cascade control.